Implementasi Blockchain Ethereum dalam Aplikasi E-Voting Berbasis Website untuk Pemilihan Koordinator Tingkat (KORTI) - Kadek Sathya Wageswara; I Nyoman Purnama; I Nyoman Yudi Anggara Wijaya (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Electronic voting improves election efficiency yet continues to face trust-related concerns stemming from centralization and the potential for data manipulation. This study develops a web-based e-voting system integrated with the Ethereum blockchain to strengthen security and transparency. The system employs Solidity smart contracts, Ganache for local network simulation, Truffle, MetaMask, and MySQL. Development follows the Waterfall model, with unit testing and black-box testing conducted as part of the verification process. Testing was carried out using 10 simulation accounts on the Ganache network. The results demonstrate a 100% success rate across all functional scenarios, in which a total of 27 votes were recorded in real-time on the verified latest block height without any transaction failure. This implementation advances immutability and auditability; however, cost analysis reveals a dependency on fluctuating gas fees should the system be deployed on the public mainnet